The Brahmin Keeps India in the 18th Century - Bedide, Naren (Prabuddha: Journal of Social Equality; Vol 2 No 1 (2018): Myths underlying brahmin supremacy and white supremacy, 2018)
In this interview, the caste mode of production is discussed as a perplexingly unexplored area of economics, politics and sociology in India. The role, relationship and negative impact of the ruling class composed of the Brahmins and upper castes on the Bahujan majority are highlighted.